1987
DOI: 10.3109/00365528708991483
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fatty Acid Composition in Patients with Ileal Dysfunction

Abstract: Chemical signs of essential fatty acid deficiency (EFD) were studied in 31 patients who has undergone an ileal resection on an average 7 years earlier by determining fatty acid composition in serum lipids. The subjects were divided into two groups in accordance with the presence (greater than 7 g/day) or absence (less than 7 g/day) of fat malabsorption. The two groups were matched for age, nutritional status, and essential fatty acid intake, but the patients with steatorrhea had higher levels of fecal bile aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although LA content is much lower in olive than in soyabean oil-based ILE, no deficiency in EFA was observed during the study period, as confirmed in both plasma and cell membrane by a triene:tetraene ratio which remained stable and below the threshold of 0•2 in all patients of both groups. It has been reported that more than 25 % of patients with malabsorption have biochemical evidence of EFA deficiency (Farkkila et al 1987;Siguel & Lerman, 1996) as well as in patients with short-bowel syndrome (Edes et al 1991;Chambrier et al 2002) or under long-term HPN (Abushufa et al 1995;Mascioli et al 1996). Conversely, the present findings indicate that a supply of LA corresponding to 18 % of the total parenteral fatty acid intake in the olive group was sufficient to maintain a normal EFA status in patients on long- oral lipids absorbed is calculated as the ratio of net absorption of fat (subtracting the amount excreted in faeces from the amount ingested)/daily oral fat intakes• † SBS due to multiple bowel resections for familial polyposis (n 1), common mesenter (n 2), arterial mesenteric infarction (n 4), Crohn's disease (n 1) or radiation enteritis (n 2), with a median post-duodenal remnant small-bowel length of 47 (range 5 -120) cm in the olive group, and of 60 (range 20-100) cm in the soya group• 18 þ C18 : 3n-6):C18 : 2n-6 ratios were established as respective estimates of essential fatty acid deficiency (Holman, 1960) and linoleic acid metabolism to higher derivatives efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although LA content is much lower in olive than in soyabean oil-based ILE, no deficiency in EFA was observed during the study period, as confirmed in both plasma and cell membrane by a triene:tetraene ratio which remained stable and below the threshold of 0•2 in all patients of both groups. It has been reported that more than 25 % of patients with malabsorption have biochemical evidence of EFA deficiency (Farkkila et al 1987;Siguel & Lerman, 1996) as well as in patients with short-bowel syndrome (Edes et al 1991;Chambrier et al 2002) or under long-term HPN (Abushufa et al 1995;Mascioli et al 1996). Conversely, the present findings indicate that a supply of LA corresponding to 18 % of the total parenteral fatty acid intake in the olive group was sufficient to maintain a normal EFA status in patients on long- oral lipids absorbed is calculated as the ratio of net absorption of fat (subtracting the amount excreted in faeces from the amount ingested)/daily oral fat intakes• † SBS due to multiple bowel resections for familial polyposis (n 1), common mesenter (n 2), arterial mesenteric infarction (n 4), Crohn's disease (n 1) or radiation enteritis (n 2), with a median post-duodenal remnant small-bowel length of 47 (range 5 -120) cm in the olive group, and of 60 (range 20-100) cm in the soya group• 18 þ C18 : 3n-6):C18 : 2n-6 ratios were established as respective estimates of essential fatty acid deficiency (Holman, 1960) and linoleic acid metabolism to higher derivatives efficiency.…”
Section: Discussionmentioning
confidence: 99%